Clinicians Report Difficulty Limiting Low-Value Services in Daily Practice - Michael Grover; Ryan McLemore; Jon Tilburt (SAGE Publishing, 2016)
Health care services that increase costs but fail to improve health are of low value. Limiting low-value services has potential to decrease health care expenditures by eliminating waste. We examined the opinions of Continuing Medical Education attendees about the "Choosing Wisely" campaign and decreasing use of potentially unnecessary services of low value. We compared our attendees' responses to those of participants who completed a survey a year earlier. Respondents acknowledged waste of resources as a common and serious problem and noted frequent opportunities to address low-value services with their patients. They also reported limited ability to successfully reduce unnecessary services in daily clinical care. Lack of familiarity with "Choosing Wisely" may be related.